Green chemistry in Argentine - Vazquez, Patricia Graciela (2014)
Green chemistry is the chemists' response to the challenges of sustainable development and to the awareness of the impacts that human activities have on the environment, and of the implications of these impacts on our own (humans?) wellbeing. The scope of green chemistry is deeply embedded in the scope of chemistry as the science of substances. The principles of green chemistry focus on substances, on the characteristics that are relevant for our health and safety (non-hazardous, non-toxic), on the way in which they are produced and on their utilisation life-span. Thus, green chemistry aims at protecting our health and the environment by selecting the types of substances preferably to be produced, the best (safer and more environmentally compatible) ways of producing them, and the best ways of utilising them.